Análisis de los gastos generados en proyectos de inversión en el Gobierno Autónomo Descentralizado Parroquial La Unión presupuesto 2018-2019 - Peralta Meza, Joselyn Natalia (2020)
The objective of the case study was to analyze the expenses generated in investment projects in the La Unión Parish Decentralized Autonomous Government of the Babahoyo province of Los Ríos in the 2018 and 2019 period, for this the inductive, deductive, analytical, statistical methods were used. A field investigation was developed since the information was obtained directly from the Finance Department of the place under study. Financial ratios were used based on the budget acquired in the Capital Income Item in the years of study, finally the main objective of the research was carried out and a comparative analysis was developed in the expenses of the item under study for the years 2018 and 2019 where it was revealed that the Parish Autonomous Decentralized Government La Unión of the Babahoyo canton, Los Ríos province, despite having obtained a budget increase in 2019 and not having an adequate well-planned strategic program, there are balances that could generate reductions in future budgets affecting directly in the development of La Unión Parish.